2013
DOI: 10.1177/1352458513507358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on fitness and cognition in progressive MS: a randomized, controlled pilot trial

Abstract: Background: Exercise may have beneficial effects on both well-being and walking ability in multiple sclerosis (MS). Exercise is shown to be neuroprotective in rodents and may also enhance cognitive function in humans. It may, therefore, be particularly useful for MS patients with pronounced neurodegeneration. Objective: To investigate the potential of standardized exercise as a therapeutic intervention for progressive MS, in a randomized-controlled pilot trial. Methods: Patients with progressive MS and moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
194
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(207 citation statements)
references
References 36 publications
9
194
1
3
Order By: Relevance
“…Over the past decade, evidence on the beneficial effects of exercise therapy has increased and today it is more and more recommended for patients with MS. [32][33][34][35][36] The beneficial effect appears to be multi-dimensional. Aerobic capacity, 37 walking mobility 38,39 and muscular strength 40 can be improved, but also QoL, 40,41 fatigue, 40,42-44 depression 45,46 and cognition 46 can be positively influenced by exercise ( Figure 4). Besides, it might currently be the only treatment option leading to symptomatic improvement for patients with progressive MS types.…”
Section: Non-medical Treatment Options: Active Rehabilitation Treatmentmentioning
confidence: 99%
“…Over the past decade, evidence on the beneficial effects of exercise therapy has increased and today it is more and more recommended for patients with MS. [32][33][34][35][36] The beneficial effect appears to be multi-dimensional. Aerobic capacity, 37 walking mobility 38,39 and muscular strength 40 can be improved, but also QoL, 40,41 fatigue, 40,42-44 depression 45,46 and cognition 46 can be positively influenced by exercise ( Figure 4). Besides, it might currently be the only treatment option leading to symptomatic improvement for patients with progressive MS types.…”
Section: Non-medical Treatment Options: Active Rehabilitation Treatmentmentioning
confidence: 99%
“…However, a more recent RCT of an aerobic exercise intervention in persons with MS reported improved cognitive function in several neuropsychological domains in subjects who received the exercise intervention, compared with a waiting list control group [Briken et al 2014]. A study using a computer/internet based intervention to increase physical activity behavior demonstrated a clinically significant increase in the Symbol Digit Modalities Test (SDMT) in a subset of subjects with mild disability at the end of the intervention while there was minimal change in this metric in a waiting list control group [Sandroff et al 2014].…”
Section: Cognitionmentioning
confidence: 99%
“…Studies have demonstrated the efficacy of a 6-week multidisciplinary rehabilitation program for patients with progressive MS and found improvements in disability, depression, fatigue, social experience and quality of life [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Briken et al reported significant improvements in mobility, depression, fatigue, and cognitive function, and Miller et al reported significant improvements in muscle strength and anxiety [6,7].…”
Section: Exercise Therapymentioning
confidence: 99%